Reversals of Reforestation Across Latin America Limit Climate Mitigation Potential of Tropical Forests - Schwartz, Naomi B.; Aide, T. Mitchell; Graesser, Jordan; Grau, H. Ricardo; Uriarte, María (Frontiers in Forests and Global Change, 2020)
Carbon sequestration through tropical reforestation and natural regeneration could make an important contribution to climate change mitigation, given that forest cover in many tropical regions increased during the early part of the 21st century. The size of this carbon sink will depend on the degree to which second-growth forests are permanent and protected from re-clearing. Yet few studies have assessed permanence of reforestation, especially not at a large spatial scale. Here, we analyzed a 14-year time series (2001-2014) of remotely-sensed land-cover data, covering all tropical Latin America and the Caribbean, to quantify the extent of second-growth forest permanence. Our results show that in many cases, reforestation in Latin America and the Caribbean during the early 21st century reversed by 2014, limiting carbon sequestration. In fact, reversals of reforestation, in which some or all gains in forest cover in the early 2000s were subsequently lost, were ten times more common than sustained increases in forest cover. This impermanence resulted in 0.44 Pg of forgone carbon sequestration, equivalent to 75% of the carbon that we estimate would have been sequestered in the same period if all new forest had persisted (0.58 Pg carbon). Differences in the prevalence of reforestation reversals across countries suggest an important role for socio-economic, political, and ecological context, with political transitions and instability increasing the likelihood of reversals. These findings suggest that national commitments to reforestation may fall short of their carbon sequestration goals without provisions to ensure long-term permanence of new forests.